Declining Orangutans Population in the Unprotected Forest of Batang Toru - Arfah Nasution; Dyah Perwitasari-Farajallah; Sri Suci Utami-Atmoko (Tropical Life Sciences Research, 2018)
Habitat loss and hunting are major threats to the long-term survival of the viable orangutan population in Batang Toru. East Batang Toru Forest Block (EBTFB) is the most threatened area due to low forest cover and high encroachment. Based on a preliminary survey in 2008, Hopong forest which is located in EBTFB, had the highest orangutan density (0.7 ind/km2). However illegal logging and hunting of protected species were occuring in this unprotected forest. Since this location has been gazetted as unprotected forest from the first survey until this study was conducted, it is important to assess orangutans population trends. This study aims to provide an updated density of orangutan in Hopong forest. The study included the location of the original survey but covered a wider overall area. The line transect method was used to record orangutan nests, ficus and trees bearing fruits. A quadrat method was used to record vegetation. The encounter rate of orangutan declined from 0.7 ind/km2 to 0.4 ind/km2 between 2008 and 2015. Forest cover has also changed in the seven years between surveys and this has influenced orangutan and orangutan nest encounter rates in Hopong. Since unprotected forest is at more risk in comparison with protected forest, allocation status of the Hopong forest is critical to reduce the threats it faces.